Lithium-ion battery module performance improvements by using nanodiamond-FE3O4 water/ethylene glycol hybrid nanofluid and fins - Dilbaz, Furkan; Selimefendigil, Fatih; Öztop, Hakan Fehmi (Springer, 2022)
Control of heat released during charge/discharge processes of lithium-ion batteries is very important for the improvement of efficiency of lithium-ion batteries. In this study, the thermal performance of a 20 Ah rectangular type battery pack is analyzed with two different cooling fluids, namely water and nanodiamond-Fe3O4 water/ ethylene glycol (ND- Fe3O4 W/EG) hybrid nanofluid. The cooling system has 5 to 25 number of fins while the Reynolds number is taken between 100 and 800. The volume fraction of the nanoparticles is between 0 and 2% while the discharge rates of 3C, 4C and 5C are considered. The findings suggest that increasing the Reynolds number and the nanoparticle volume ratio improves the temperature distribution and lowers the maximum temperature in the battery pack. When compared to water with the same Re number, ND-Fe3O4 + W/EG hybrid nanofluid with 2% volume ratio at 800 Re number provides improvement of maximum temperature by 23.1% while 70.35% improvement in temperature difference is achieved. Using higher number of fins improves the performance. There is a reduction of 13.8% of the temperature difference in the battery pack with 25 fin model as compared to 5 fin model.
Keywords: Battery cooling; Finite element method; Hybrid nanofluid; Cooling system; CFD; Energy storage